Controlled Synthesis and Photonics Applications of Metal Halide Perovskite Nanowires. Issue 1 (4th October 2018) - Zhang, Xuehong; Chen, Shula; Wang, Xiao; Pan, Anlian
Abstract: Metal halide perovskite nanowires (NW)s have recently demonstrated potential applications in integrated photonics devices such as lasers and photodetectors due to their unique physical and chemical characteristics. Here, the rapid progress in the synthesis methods and photonics applications of organic–inorganic hybrid and all‐inorganic halide perovskite NWs are reviewed systematically. The controlled synthesis methods are mainly classified into solution‐phase synthesis, vapor‐phase synthesis, and other synthesis methods. The photonics applications of the halide perovskite NWs, including lasers, photodetectors, solar cells, and other applications, are also introduced and discussed. Finally, the summary and perspectives for halide perovskite NWs are provided. Abstract : Metal halide perovskite nanowires have recently attracted great attentions due to their superior optical and optoelectronic properties. Here, the research progresses in the controlled synthesis of the halide perovskite nanowires are reviewed. Their advanced applications in optical and optoelectronics are also discussed systematically. The perspectives of future directions in perovskite nanowire research are also given.